2012
DOI: 10.1017/s0031182012001783
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of cercarial development and emergence in trematodes

Abstract: SUMMARY Temperature is an important factor influencing the biology of ectothermic organisms and is intrinsically linked to climate change. Trematodes are potentially susceptible to temperature changes and in order to develop predictive frameworks of their responses to climate change large-scale analyses are needed. The present study, using the Q 10 value, analyses experimental data from the scientific literature on the effects of temperature on cercarial development and emergence across a wide range of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 65 publications
(60 reference statements)
5
74
0
1
Order By: Relevance
“…This conclusion coincides with the proposal in the review of Morley & Lewis (2013) that midlatitude species (i. e., from between 36 and 60°), such as those studied here, exhibit an optimum temperature of emergence from 15 to 25 °C. Therefore, from the results of the present study and the observations of the earlier work cited above, an elevation in ambient temperature cannot be said to enhance cercarial shedding in general; rather, the effect of temperature on emergence is a trematode-specific phenomenon.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This conclusion coincides with the proposal in the review of Morley & Lewis (2013) that midlatitude species (i. e., from between 36 and 60°), such as those studied here, exhibit an optimum temperature of emergence from 15 to 25 °C. Therefore, from the results of the present study and the observations of the earlier work cited above, an elevation in ambient temperature cannot be said to enhance cercarial shedding in general; rather, the effect of temperature on emergence is a trematode-specific phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, Morley et al (2010) found that the shedding of Echinoparyphium recurvatum, after first increasing with elevations in temperature, stabilized within the range of 17 to 25 °C, and after that plateau decreased at temperatures above 25 °C. This latter decline in emergence is consistent with our own observations but differs from the findings of Schmidt & Fried (1996), whose results coincided with those of Poulin (2006) -namely, that "an increase of a few degrees in environmental temperatures should lead to marked increases in cercarial emergence from the snail's first intermediate hosts", but, we must advise that these studies have been indicated by Morley & Lewis (2013) to be likely associated with inadequate acclimation of snails to experimental conditions. Our results and the comparable findings of Morley et al (2010) would indicate that the emergence and resulting abundance of freshwater cercariae in temperate climates are not necessarily increased by an elevation in temperature above 25 °C.…”
Section: Discussionsupporting
confidence: 88%
“…A detailed analysis by Morley and Lewis (2013) suggested that temperature might have only limited or no direct effect on cercarial emergence. As the level of infection of the bivalve second intermediate hosts directly depends on the numbers of infective cercariae at a given site, its dependence on temperature would also be rather weak.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the effect of temperature, it is known that a temperature above 10°C is essential for egg laying by G. truncatula [25]. Recent studies have looked at the effects of temperature on snail growth and the development of eggs, miracidial and intramolluscan stages of F. hepatica [26][27][28] whereas no studies are available on the effects on the population dynamics of G. truncatula. Our study suggest that in regions with a temperate climate, once temperature is higher than 10°C, rainfall is the main driver of G. truncatula abundance and temperature has no large influence.…”
Section: Discussionmentioning
confidence: 99%